COMO COSECHAR MAS FRIJOL EN EL TROPICO - SERRANO P, JOSE LUIS; CARDENAS R, FRANCISCO (Instituto Nacional de Investigaciones Agrícolas, S.A.G., 1965)
no
CAMPO
Keywords: COSECHAR, FRIJOL, TROPICO; CIENCIAS AGRARIAS; AGRONOMIA; PRODUCCION DE CULTIVOS